Community Acquired Pneumonia; Chest X-Ray Findings in Three Different Times (Medico Legal Update, 2020)
Introduction: community acquired pneumonia is common health problem with concerns regarding chest-X-ray findings in different occasions during the disease course. The aim of this study is to compare chest-X-ray findings at presentation, 3 days and 6 weeks after presentation.Methods: A prospective, observational study was conducted. The consecutive cases of single center were collected from January 2016 to January 2017. The diagnosis was made whenever there was new infiltrate in the CXR with compatible clinical features. All patients with nosocomial infection were excluded from the study. The included data were demographic characters, history, clinical examination, and CXR findings. Results: The study included 60 patients, 44(73.3%) were male while 16(26.7%) were female. The age of the patients ranged from 19 to 87 years with a mean age of 57.81 years. Chronic obstructive pulmonary disease (COPD) is the most concomitant respiratory disease (11, 18.3%), followed by asthma (9, 15%), and pulmonary fibrosis (9, 15%), other 6 cases (10%) had history of bronchogenic carcinoma, while pulmonary tuberculosis (TB) was found in 3 cases (5%). Cough was the most common presenting symptom which was found in all the cases (60, 100%). Smoking did not correlated with the CXR findings significantly at presentation, 3 days and 6 weeks post complaint (P-value 0.189,0.185 , 0.265 respectively). The most common side of affection was right upper zone which was found in 20 (33.3%) cases. Severity of the CAP significantly related to the pattern of pulmonary involvement which was evident in the CXR (P-value 0.000). Conclusion: community acquired pneumonia is usually diagnosed by compatible clinical presentation and radiological characteristics. Timing of CXR influences its role in both diagnosis and follow up.